DAMPAK PADI TRANSGENIK MENGEKSPRESIKAN GEN cryIA(b) UNTUK KETAHANAN TERHADAP PENGGEREK BATANG DI LAPANG TERBATAS TERHADAP SERANGGA BUKAN SASARAN - Enung S. Mulyaningsih, Puspita Deswina dan Inez H. Slamet-Loedin . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2009)
The impact of transgenic rice expressing cryIA(b) gene for stem borer resistance at limited field to non target insects. Transgenic rice plant Rojolele cultivar (lines 6.11(+), 6.11-48, 6.11, 11.21-39, and 11.21-48) that contain cryIA(b) gene from Bacillus thuringiensis was obtained. These lines were expected resistance to stem borer that is considered as one of primary pests. At seven (T6) generation, limited field trial was conducted in Karawang-West Java. Cilosari cultivar (medium resistant control) and IR 62 (susceptible control) were included as standars as well as a non transformed cultivar Rojolele isogenic control and border along with other plants in the surrounding area. The testing was done to meet the biosafety requirements as stipulated in Assessment Guidelines of Living Modified Organism Biosafety Plant Series. Observation was carried out on non targert insect such as other pest insect and general predator in the field. The results showed that non target pest insect white back planthopper (WBP) and bug rice (Leptocorisa oratorius F.) were found in the field with different levels attacks in accordance with their respective population. WBP attacked since the beginning of the planting. WBP population in transgenic plant at the end of the observation indicated the same level of vulnerability as Rojolele control and both were more vulnerable that Cilosari and IR 62. The rice bug attack when plant at tiller filling (immature seed) therefore the data could not be compared with Cilosari and IR 62 because both of cultivars were shorter age than Rojolele. However, the population of L. oratorius between transgenic and control were not significant different. There are three genera of generalist predator observed such as Paederus, Coccinella, and Cyrthorinus. These population were not significant different in all transgenic lines tested (Rojolele control, Cilosari, and IR 62). Thus the results of the experiment proved that transgenic lines tested in Karawang did not have negative impact on the population of other insects.